Structural transformation in Zr/Mg multilayer on Si substrate after annealing - Konotopsky, L.E.; Kopilets, I.A.; Kosmachev, S.M.; Kondratenko, V.V. (Вопросы атомной науки и техники, 2018)
A Zr/Mg periodic multilayer was deposited onto silicon substrate by DC magnetron sputtering. Study of the Zr/Mg multilayer structure in an initial state and after thermal annealing in a temperature range of 100...600 °C was made by the X-ray diffraction and cross-section transmission electron microscopy methods. It was shown that Zr/Mg multilayers are stable up to 400 °C. Further heating to 500 °C leads to decreasing of the number of the operable periods due to the zirconium and magnesium layers interaction with the silicon substrate. Annealing at 550 °C leads to multilayer periodicity destructing. Рентгенографічними і електронно-мікроскопічними методами досліджено багатошарове рентгенівське дзеркало (БПК) Zr/Mg у вихідному стані та після відпалу (100…600 °С). БПК Zr/Mg на кремнієвій підкладці було виготовлено методом прямоточного магнетронного розпилення. Показано, що структура рентгенівського дзеркала зберігається незмінною при відпалі до 400 °С. Подальший нагрів до 500 °С супроводжується зниженням числа робочих періодів за рахунок взаємодії шарів цирконію і магнію з кремнієвої підкладкою. Відпал при 550 °C призводить до руйнування періодичної структури в БПК. Рентгенографическими и электронно-микроскопическими методами исследовано многослойное рентгеновское зеркало (МРЗ) Zr/Mg в исходном состоянии и после отжига (100…600 °С). МРЗ Zr/Mg на кремниевой подложке было изготовлено методом прямоточного магнетронного распыления. Показано, что структура рентгеновского зеркала сохраняется неизменной при отжиге вплоть до 400 °С. Дальнейший нагрев до 500 °С сопровождается снижением числа рабочих периодов за счет взаимодействия слоев циркония и магния с кремниевой подложкой. Отжиг при 550 °C приводит к разрушению периодической структуры в МРЗ.